2021
DOI: 10.3390/jcm10112518
|View full text |Cite
|
Sign up to set email alerts
|

Does the Addition of Pain Neurophysiology Education to a Therapeutic Exercise Program Improve Physical Function in Women with Fibromyalgia Syndrome? Secondary Analysis of a Randomized Controlled Trial

Abstract: Therapeutic exercise (TE) is one of the most investigated approaches for the management of FMS. Pain neurophysiology education (PNE) helps toward understanding the pain condition, leading to maladaptive pain cognitions and coping strategies in patients with chronic pain. Our study aimed to assess the effects of therapeutic exercise and pain neurophysiology education versus TE in isolation on fatigue, sleep disturbances, and physical function in the short term and at three months of follow-up in women with fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The most-investigated strategy was the individual or group self-management course/program, investigated in 52% of the studies [ 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], which encompassed a mix of the remaining strategies. Following, the order of the most-investigated strategies was physical exercise (in 34% of the studies), that could be specific [ 32 , 52 , 53 , 54 , 55 ] or general exercises [ 20 , 21 , 25 , 35 , 48 , 49 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], individually or in groups, followed by education (in 21% of the studies) [ 21 , 32 , 36 , 52 , 53 , 54 , 56 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most-investigated strategy was the individual or group self-management course/program, investigated in 52% of the studies [ 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], which encompassed a mix of the remaining strategies. Following, the order of the most-investigated strategies was physical exercise (in 34% of the studies), that could be specific [ 32 , 52 , 53 , 54 , 55 ] or general exercises [ 20 , 21 , 25 , 35 , 48 , 49 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], individually or in groups, followed by education (in 21% of the studies) [ 21 , 32 , 36 , 52 , 53 , 54 , 56 ...…”
Section: Resultsmentioning
confidence: 99%
“…Self-strategies investigated resulted in the reduction of pain intensity and/or the number of spots presenting pain. In second place were increased self-care, self-efficacy, self-management and/or health behaviors (24.14%) [ 26 , 33 , 36 , 37 , 39 , 42 , 45 , 51 , 53 , 54 , 55 , 56 , 57 , 59 , 73 , 79 ], followed by increased physical function (20.68%) [ 19 , 20 , 21 , 28 , 34 , 36 , 40 , 42 , 45 , 52 , 56 , 58 , 61 , 62 , 73 ] and reduced depression (18.96%) [ 26 , 29 , 30 , 32 , 35 , 37 , 39 , 49 , 66 , 68 , 70 ]. Table 2 presents some examples of positive findings of the studies included, organized according to the main aspect addressed by their outcomes: biological, psychological, social or a mix of them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the impact of kinesiophobia has been examined in various musculoskeletal diseases, there is no evidence of how kinesiophobia influences postural control in individuals with FM [ 31 , 32 ]. Therefore, the objectives of this study were to (1) estimate and compare the postural control variables between asymptomatic individuals and individuals with FM, (2) to assess the relationship between kinesiophobia and postural control in individuals with FM, and (3) to assess whether pain intensity mediates the relationship between kinesiophobia and postural control in individuals with FM.…”
Section: Introductionmentioning
confidence: 99%
“…This association between interventions should be encouraged. A clinical trial by Ceballos-Laita et al (2021) found that pain education combined with physical exercise therapy appears to be more effective than physical exercise alone for improving physical function in women with fibromyalgia in the short term.…”
Section: Introductionmentioning
confidence: 99%